Mannich and O-Alkylation Reactions of Tetraalkoxyresorcin[4]arenes. The Use of Some Products in Ligand-Assisted Reactions - Buckley, B.; Boxhall, J.; Page, P.; Chan, Y.; Elsegood, M.; Heaney, H.; Holmes, K.; Mcildowie, M.; McKee, V.; McGarth, M.; Mocerino, Mauro; Poulton, A.; et al. (Wiley-VCH Verlag GMBH, 2006)
The measurement of the pKa of racemic tetramethoxyresorcin[4]arenes explains the failure to obtain good yields in attempted Mannich reactions of these substrates under classical reaction conditions. The failure is related to the lack of adequate concentrations of the iminium ions that results from the reduced acid strength of tetraalkoxyresorcin[4]arenes compared with that of the parent octahydroxyresorcin[4]arenes. However, the preparation of a series of Mannich bases derived from racemic tetraalkoxyresorcin[4]arenes was accomplished under microwave-assisted aprotic reaction conditions and the use of preformed iminium ion intermediates. When the reactions were carried out with the use of chiral bis(aminol) ethers, mixtures of diastereomers were obtained that could be separated by flash chromatography. The absolute configurations of the enantiomerically pure tetrabenzoxazine derivatives were established in some cases by X-ray crystallographic analysis and by a comparison of the nuclear magnetic resonance spectroscopic data. The alkylation of racemic tetramethoxyresorcin[4]arenes was achieved with the use of an excess of 2-bromo-N-[(R)-(+)-(a-methylbenzyl)] acetamide in acetonitrile containing potassium carbonate. Enantioselective ligand-assisted reactions of aromatic aldehydes are also reported with the use of dialkylzinc reagents both in the absence and in the presence of terminal alkynes.